Photo-click living strategy for controlled, reversible exchange of biochemical ligands - Gandavarapu, Navakanth R (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.